Answer:
i can assure you that this answer is correct on edge, enjoy !!brainliest would be appreciated ^^(2021)
Step-by-step explanation:
Are you good in the brain im your teacher and i see that you are trying to cheat
Answer:
Slope = -3/4
y-intercept = 2
Step-by-step explanation:
![3x+4y = 8\\\therefore 4y = -3x +8\\\therefore y = \frac{-3}{4}x+ \frac{8}{4}\\\therefore y = \frac{-3}{4}x+2\\Equating \: it \: with\: \\y=mx+b\\Slope\:(m) = \frac{-3}{4}\\y-intercept\:(b) = 2](https://tex.z-dn.net/?f=3x%2B4y%20%3D%208%5C%5C%5Ctherefore%204y%20%3D%20-3x%20%2B8%5C%5C%5Ctherefore%20y%20%3D%20%5Cfrac%7B-3%7D%7B4%7Dx%2B%20%5Cfrac%7B8%7D%7B4%7D%5C%5C%5Ctherefore%20y%20%3D%20%5Cfrac%7B-3%7D%7B4%7Dx%2B2%5C%5CEquating%20%5C%3A%20it%20%5C%3A%20with%5C%3A%20%5C%5Cy%3Dmx%2Bb%5C%5CSlope%5C%3A%28m%29%20%3D%20%5Cfrac%7B-3%7D%7B4%7D%5C%5Cy-intercept%5C%3A%28b%29%20%3D%202)
Answer:
B
Step-by-step explanation:
Dean recorded the results of spinning the spinner 60 times:
- Number 1 spun 12 times
- Number 2 spun 17 times
- Number 3 spun 15 times
- Number 4 spun 16 times
The <u>experimental probability</u> is the ratio of the number of times an event occurs to the total number of trials or times the activity is performed.
Find all experimental probabilities:
![P_{1}=\dfrac{12}{60}=\dfrac{1}{5}\\ \\P_{2}=\dfrac{17}{60}\\ \\P_3=\dfrac{15}{60}=\dfrac{1}{4}\\ \\P_4=\dfrac{16}{60}=\dfrac{4}{15}](https://tex.z-dn.net/?f=P_%7B1%7D%3D%5Cdfrac%7B12%7D%7B60%7D%3D%5Cdfrac%7B1%7D%7B5%7D%5C%5C%20%5C%5CP_%7B2%7D%3D%5Cdfrac%7B17%7D%7B60%7D%5C%5C%20%5C%5CP_3%3D%5Cdfrac%7B15%7D%7B60%7D%3D%5Cdfrac%7B1%7D%7B4%7D%5C%5C%20%5C%5CP_4%3D%5Cdfrac%7B16%7D%7B60%7D%3D%5Cdfrac%7B4%7D%7B15%7D)
Hence, option B is correct
![\mathfrak{\huge{\pink{\underline{\underline{AnSwEr:-}}}}}](https://tex.z-dn.net/?f=%5Cmathfrak%7B%5Chuge%7B%5Cpink%7B%5Cunderline%7B%5Cunderline%7BAnSwEr%3A-%7D%7D%7D%7D%7D)
Actually Welcome to the Concept of the Functions.
Let's first find the g(-1),
so we get as
3(-1)^2 +5(-1)-6
=> 3 -5-6
=> -8
now since g(-1) =-8
let's find f(g(-1)) that is f(-8)
f(-8) = 4(-8) + 14
=> f(g(-1)) = -32+14
=> f(g(-1)) = -18
-18 is the answer.